Activating the transportation potential of greenways in Saudi Arabia: a case study of Jeddah City - Zawawi, Abdulrahman A. (2024)
Since the early 1970s, auto-centric planning in Saudi Arabia (SA) has led to car-dependent lifestyles, resulting in health and environmental problems. In the past decade, ambitious policies (e.g., The Saudi Vision 2030), urban design manuals, awareness campaigns, city plans and projects have sought to address this problem by transitioning to sustainable urban mobility. Active transportation (AT) via networks of greenways is a dimension of such a transition and is currently being planned and advocated in Saudi cities. However, current walking and bicycling rates for transportation in SA are extremely low. Simultaneously, there is limited research on greenways in SA, and none has explored the influences on their usage as AT corridors (ATCs). An enhanced understanding of such factors is vital because academic journals found minimal effect on AT over the last thirty years from many greenway investments in various regions worldwide. Therefore, this PhD research aimed to explore the activation barriers and strategies of greenways’ function as facilitators for AT in SA, using Jeddah city as a case study.